First Record Sparus aurata Larvae in Teluk Penyu Beach Cilacap, Indonesia, revealed by DNA Barcoding - Nuryanto, Agus; Bhagawati, Dian; Winarni, Elly Tuti; Mahmoud, Hanan Hassan Alsheikh (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Morphological identification often fails to reveal the taxonomic status of fish larvae. DNA barcoding using particular DNA segment is frequently successful in solving the faulty and might reveal overlooked species, including species outside their recognized geographic ranges, such as Eastern Atlantic seabream Sparus aurata. This study aims to assess fish larvae diversity in Teluk Penyu Beach, Cilacap Central Java, Indonesia, through the cytochrome c oxidase 1 barcoding. Fish larvae were collected using a larva net with a diameter of 60 cm and height of 150 cm and horizontal towing during the field trips in March and April 2021. Larvae morphotypes were determined based on their general morphological performance observed under a magnification lens according the available references. Eighteen larvae morphotypes were successfully barcoded, and 5% genetic distance was used as a species border. Fourteen fish larvae species were revealed, with intraspecific genetic distances between 0.00% and 4.12%, while intrageneric genetic distances ranged from 5.50% to 19.29%. An interesting finding was that one larva morphotype was barcoded as S. aurata with high genetic identity (99.19% to 99.68%) and low genetic distance (0.32% to 0.81%). The discovery provides the first new data on S. aurata in Teluk Penyu Beach Cilacap, Central Java, outside its recognized geographic range. Overall, this study provides information about fish larvae in Teluk Penyu Beach, essential for estimating the number and species of fish recruited in the southern Cilacap, which is vital for fisheries management. Nevertheless, new research requires further clarification of S. aurata in Teluk Penyu Beach.